Экология грушевых тлей рода анурафис (Anuraphis Guercio) в Крыму - Колесова, Д.А. (Вестник зоологии, 1972)
Ecological peculiarities are described of pear aphids of the genus Anuraphis Guer-cio: A. farfarae Koch., A. pyrilaseri Shap.,
A. subterranea Walk., A. cantoni
H. R. L., which are developed on pear in two generations. The progeny of the fundatrix migrates on different herbaceous plants. A. farfare Koch has two populations in the Crimea: remigrating on pear in autumn and not remigrating, developing parthenogene-tically (during the whole year) only on Tussilago farfarae L.